Disorders of overeating - Stunkard, Albert (Henry Stewart Talks, 2007)
Overeating and undereating, The hypothalamus, Satiety and hunger, Binge eating: symptoms, treatment and placebo response, Night eating syndrome (NES): provisional criteria, NES onset and stress, psychosocial factors and symptoms, Which came first: night eating or obesity?, Night eating is a pathway to obesity, Circadian rhythms, Case studies, Treatment